Penyuluhan hukum tentang kepastian hukum kepemilikan tanah di Desa Empus Kecamatan Bahorok Kabupaten Langkat - Sipahutar, Ervina Sari; Siregar, Roswani; Umi Kalsum, Eka; Humaira, Rafiqah (LPPM Universitas Al-Azhar medan, 2025)
Community-based legal education is a vital strategy for enhancing public awareness of land ownership rights. This study aims to evaluate the effectiveness of lecture and discussion methods in improving the understanding of Empus Village residents, Bahorok Subdistrict, Langkat Regency, regarding the importance of land registration, and to identify challenges encountered during the program implementation. A descriptive qualitative approach was employed, involving 28 participants. Data were analyzed using a paired t-test to assess significant changes in participants' understanding before and after the activity. The findings revealed that lecture and discussion methods effectively improved participants' understanding, with average scores increasing from 43.25 to 73.25. Statistical analysis showed significant improvement with a ????-value of 14.72 and a ????-value < 0.001. However, challenges such as limited access to legal information, stigma towards land institutions, and insufficient human resources with expertise in land law remain. This study contributes to the development of community-based legal education and provides recommendations to enhance the effectiveness of similar programs in the future